2010
DOI: 10.25182/jgp.2010.5.2.87-94
|View full text |Cite
|
Sign up to set email alerts
|

Pengendalian Kadar Glukosa Darah Oleh Teh Hijau Dan Atau Teh Daun Murbei Pada Tikus Diabetes

Abstract: <p class="MsoNormal" style="margin: 0cm 7.1pt 6pt 14.2pt; text-align: justify; text-indent: 1cm;"><span style="font-size: 10pt;">Diabetes mellitus is degeneratif disease with high prevalence that happens in many countries. Several studies had been done to control diabetes by using green tea, mullberry leaf  tea, and their mixture. The aim of this research was to analyze the influence of the administration green tea, mullbery leaf tea, and their mixtures to blood glucose level of diabetic rats both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Alloxan that was induced to make normal rats became diabetic had a success rate of ±8%. If diabetic effect did not appear in 5 days after injection, re-injection was done (Efendi et al 2010). Furthermore, the rats were fed with feed pellets and given drink in ad libitum until the day 10.…”
Section: Methodsmentioning
confidence: 99%
“…Alloxan that was induced to make normal rats became diabetic had a success rate of ±8%. If diabetic effect did not appear in 5 days after injection, re-injection was done (Efendi et al 2010). Furthermore, the rats were fed with feed pellets and given drink in ad libitum until the day 10.…”
Section: Methodsmentioning
confidence: 99%
“…), Cinnamon (Cinannamomum burmanii Blume), salam (Syzygium polyanthum), mulberry (Morus canva), green tea (Camellia sinensis), green grass jelly (Premna oblongifolia L. Merr), avocado (Persea americana Mill), and red ginger (Zingiber officinale var. Rubrum) [8][9][10][11][12][13][14]. Anggorowati et al [15] reported that herbal tea made of avocado leaves dried for 30 minutes at 40ºC has an antioxidant content of 24.863 µg/mL.…”
Section: Introductionmentioning
confidence: 99%
“…Mulberry (Morus alba L.) has been reported as a source of glucose inhibitors (Efendi et al 2010) and widely used for various diseases such as diabetes, hyper cholesterolemia, and kidney diseases (Huang et al 2013). The beneficial properties of the plant are attributed to its active compounds such as alkaloid, flavonoid, polyphenol, Calcium, Phosphor, Iron, Manganese, vitamins (A, B, C).…”
Section: Introductionmentioning
confidence: 99%